(untitled) (Experimental biology, 2009)
At influence on animals a dust of uranium ore doses equal 5, 10 and 50 maximum concentration limits ultrastructural changes of respiratory department of lungs had the various characteristic of development and expressiveness of pathological process. At a dose 5 maximum concentration limits of an inhalation priming the recession period was quickly replaced by the adaptation and protection period. At a dose 10 maximum concentration limits the recession phase had the big duration, being replaced for a certain time by a restoration phase respiratory department of lungs. Influence by a dose 50 maximum concentration limits led to heavy submicroscopic changes at once in 3 days, and in the subsequent terms in respiratory department of easy experimental animals against heavy destructive changes developed and amplified adaptive reactions.